Sintered body and method for producing the same
The fracture toughness value was measured by the SEPB method and the zirconia sintered body containing stabilizer and additive components was used to solve the problems of high brittleness and low reliability in measuring fracture toughness, and a sintered body with high fracture toughness and mechanical strength was achieved.
Patent Information
- Application Number
- CN202180030251.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-10-26
- Filing Date
- 2021-04-20
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2041-04-20
AI Technical Summary
The existing zirconia sintered bodies have high brittleness in decorative applications, which is difficult to meet the needs of high fracture toughness. At the same time, there are problems of diversity and low reliability in the measurement methods of fracture toughness.
The fracture toughness value was measured by the SEPB method, and a sintered zirconia containing a stabilizer was used, with a monoclinic crystallinity of more than 0.5%, and a three-point bending strength was greater than 1450MPa. Added components such as alumina, germanium dioxide and silica were added to the sintered body.
A sintered body with high fracture toughness value and mechanical strength has a higher fracture toughness value than a zirconium oxide sintered body containing yttrium oxide less than 2.0 mol% or less.
Smart Images

Figure GDA0003901888260000361 
Figure GDA0003901888260000381 
Figure GDA0003901888260000391
Abstract
Description
Technical Field
[0001] The present invention relates to a sintered body with zirconium oxide as a main phase and a method for producing the same. Background Art
[0002] In addition to conventional uses of zirconia sintered bodies that require strength, such as pulverizing media and structural materials, applications for decorative uses such as decorative parts for watches, portable electronic devices, automobiles, and home appliances are being studied.
[0003] Sintered bodies used for decorative purposes require reduced brittleness, that is, increased fracture toughness values.
[0004] Various zirconia sintered bodies have been reported so far for the purpose of improving the fracture toughness value. For example, Patent Document 1 describes a zirconia-alumina composite sintered body obtained by mixing a commercially available zirconia powder containing 3 mol% yttria produced by a neutralization coprecipitation method with a commercially available alumina powder to obtain a mixed powder, and subjecting the mixed powder to microwave sintering. The fracture toughness value (K IC ) is 6.02~6.90MPa·m 1 / 2 .
[0005] Patent Document 2 describes a zirconia sintered body obtained by hot isostatic pressing (HIP) of zirconia powder containing phosphorus, silicon dioxide, and aluminum oxide. The sintered body is described as having a fracture toughness value of 6 to 11 MPa·m as measured by the method specified in JIS R 1607. 1 / 2 .
[0006] Prior Art Literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2017-226555
[0009] Patent Document 2: Japanese Patent Application Laid-Open No. 2011-178610 Summary of the invention
[0010] (Problems to be solved by the invention)
[0011] When applied to decorative parts, it is also required to evaluate the brittleness of the sintered body with a fracture toughness value with high reliability. In contrast, even if the fracture toughness measurement method is standardized, there are multiple methods, and the values obtained by each measurement method are very different. The fracture toughness value of Patent Document 1 is a value measured by a simple method, and the fracture toughness value measurement method of Patent Document 2 is unclear, and the disclosed values are all of low reliability.
[0012] An object of the present invention is to provide a zirconia sintered body having a high fracture toughness value measured by the SEPB method and high mechanical strength, and a method for producing the same, and at least one of a zirconia sintered body having a higher fracture toughness value than a conventional yttria-containing zirconia sintered body containing 2.0 mol % or less of yttria.
[0013] (Technical solutions to solve problems)
[0014] The present invention is described in the claims, and the gist of the present invention is as follows.
[0015] [1] A sintered body comprising zirconium oxide containing a stabilizer, wherein the monoclinic crystal ratio of the sintered body is 0.5% or more and the three-point bending strength determined by a three-point bending test in accordance with JIS R 1601 is greater than 1450 MPa.
[0016] [2] The sintered body according to [1] above, wherein the total light transmittance with respect to light of a wavelength of 600 nm is 20% or more when the sample thickness is 1.0 mm.
[0017] [3] Based on the sintering described in [1] or [2] above, the ratio of the area intensity of the XRD peak corresponding to the (11-1) plane of monoclinic zirconia to the area intensity of the XRD peak corresponding to the (111) plane of monoclinic zirconia is greater than 0.
[0018] [4] In the sintered body described in any one of [1] to [3] above, the stabilizer is one or more selected from yttrium oxide, calcium oxide, magnesium oxide and cerium oxide.
[0019] [5] In the sintered body according to any one of [1] to [4] above, the content of the stabilizer is 1.0 mol% or more and less than 2.5 mol%.
[0020] [6] In the sintered body described in any one of [1] to [4] above, the content of the stabilizer is 1.0 mol% or more and less than 1.9 mol%.
[0021] [7] A sintered body according to any one of [1] to [6], wherein the fracture toughness value measured by the SEPB method specified in JIS R1607 is 6 MPa·m 0.5 Above and 11MPa·m 0.5 the following.
[0022] [8] The sintered body according to any one of [1] to [7] above, wherein the offset value of the tetragonal zirconia (113) plane is 0.15° or more.
[0023] [9] The sintered body according to any one of [1] to [8] above, further comprising one or more additional components selected from the group consisting of alumina, germanium dioxide and silicon dioxide.
[0024]
[10] In the sintered body described in any one of [1] to [9] above, the added component is alumina.
[0025]
[11] In the sintered body described in any one of [1] to
[10] above, the zirconium oxide includes at least one of monoclinic zirconium oxide, tetragonal zirconium oxide, and cubic zirconium oxide.
[0026]
[12] Based on the sintered body described in any one of the above [1] to
[11] , the ratio of the tetragonal crystal ratio of the sintered body after immersion in hot water at 140°C for 6 hours to the tetragonal crystal ratio before immersion in hot water at 140°C for 6 hours is 15% or more.
[0027]
[13] A method for producing a sintered body as described in any one of [1] to
[12] above, comprising the following steps: a step of sintering a powder containing zirconium oxide with a monoclinic fraction greater than 70% and a stabilizer, wherein the crystallite diameter of the monoclinic zirconium oxide is greater than 23 nm and less than 80 nm, to produce a pre-sintered body with a relative density of less than 99%; and a step of pressure sintering the pre-sintered body.
[0028]
[14] In the manufacturing method described in
[13] above, the pressurization treatment is hot isostatic pressing.
[0029]
[15] A component comprising the sintered body described in any one of [1] to
[12] above.
[0030] (Effects of the Invention)
[0031] According to the present invention, it is possible to provide a zirconia sintered body having a high fracture toughness value measured by the SEPB method and high mechanical strength, and a method for producing the same, and at least one of a zirconia sintered body having a higher fracture toughness value than an existing yttria-containing zirconia sintered body containing 2.0 mol % or less of yttria. DETAILED DESCRIPTION
[0032] Hereinafter, the present invention will be described by showing an example of embodiment.
[0033] The terms in this embodiment are as follows.
[0034] "Monoclinic ratio" and "tetragonal ratio" are the ratios of monoclinic zirconia and tetragonal zirconia in the crystalline phase of zirconia, respectively. In addition, "monoclinic intensity ratio" is the ratio of the area intensity of the XRD peak corresponding to the (11-1) plane of monoclinic zirconia in the crystalline phase of zirconia to the area intensity of the XRD peak corresponding to the (111) plane of monoclinic zirconia.
[0035] Regarding the powder, the powder X-ray diffraction (hereinafter also referred to as "XRD") pattern of the powder is used. On the other hand, regarding the sintered body, the XRD pattern of the surface of the sintered body after mirror polishing (hereinafter also referred to as "mirror sintered body") is used. The monoclinic crystal ratio can be calculated by the following formula (1), the tetragonal crystal ratio can be calculated by the following formula (2), and the monoclinic crystal intensity ratio can be calculated by the following formula (3).
[0036] f m = {I m (111)+I m (11-1)} / [I m (111)+I m (11-1)+I t (111)+I c (111)]×100(1)
[0037] f t =I t (111) / [I m (111)+I m (11-1)+I t (111)+I c (111)]×100 (2)
[0038] M (11-1) / (111) = {I m (11-1) / I m (111)} (3)
[0039] In formulas (1) to (3), f m is the monoclinic ratio (%), f t is the tetragonal crystal ratio (%), M (11-1) / (111) is the monoclinic intensity ratio, I m (111) and I m (11-1) are the area intensities of the XRD peaks corresponding to the (111) and (11-1) planes of monoclinic zirconia, respectively. t (111) is the area intensity of the XRD peak corresponding to the (111) plane of tetragonal zirconia, and I c (111) is the area intensity of the XRD peak corresponding to the (111) plane of cubic zirconia.
[0040] The following conditions can be mentioned as the conditions for measuring the XRD pattern.
[0041] Radiation source: CuKα radiation (λ = 0.15418nm)
[0042] Measurement mode: continuous scan
[0043] Scanning speed: 4° / min
[0044] Step size: 0.02°
[0045] Measuring range: 2θ=26°~33°
[0046] In the above-mentioned XRD pattern measurement, it is preferable to measure the XRD peak corresponding to each crystal plane of zirconium oxide as a peak having a peak top at the following 2θ.
[0047] XRD peak corresponding to the (111) plane of monoclinic zirconia: 2θ = 31 ± 0.5°
[0048] XRD peak corresponding to the (11-1) plane of monoclinic zirconia: 2θ = 28 ± 0.5°
[0049] The XRD peaks corresponding to the (111) plane of tetragonal zirconia and cubic zirconia were repeatedly measured, and the 2θ of the peak top was 2θ=30±0.5°.
[0050] The area intensity of the XRD peak of each crystal plane can be determined by separating each XRD peak using "PRO-FIT" in a calculation program according to the method described in H. Toraya, J. Appl. Crystallogr., 19, 440-447 (1986).
[0051] In addition, the "mirror-finished sintered body" provided for the above-mentioned XRD measurement is a sintered body in the following state: that is, after cutting the sintered surface using a surface grinder, the measuring surface is mirror-polished in the order of automatic polishing using grinding cloth and paper, automatic polishing using diamond slurry with an average particle size of 3 μm, and automatic polishing using colloidal silica with an average particle size of 0.03 μm, thereby obtaining a sintered body with a surface roughness Ra of less than 0.04 μm.
[0052] The “crystallite diameter of monoclinic zirconia” in the powder (hereinafter also referred to as “D m ”) is a value obtained from the XRD pattern of the powder using the following formula (4), and the “crystal diameter of tetragonal zirconia” (hereinafter also referred to as “D t ”) is a value obtained from the XRD pattern of the powder using the following formula (5).
[0053] D m =κλ / (βcosθ m) (4)
[0054] D t =κλ / (βcosθ t ) (5)
[0055] In formula (4) and formula (5), D m is the crystallite diameter of monoclinic zirconia (nm), D t is the crystallite diameter of tetragonal zirconia (nm), κ is the Scherrer constant (κ=1), λ is the wavelength of the light source used in XRD measurement (nm), β is the half-value width after correction for mechanical expansion using quartz sand with a particle size of 25 to 90 μm (manufactured by Wako Pure Chemical Industries, Ltd.) (°), and θ m is the Bragg angle (°) of reflection corresponding to the (11-1) plane of monoclinic zirconia in XRD measurement, and θ t It is the Bragg angle (°) of reflection corresponding to the (111) plane of tetragonal zirconia in XRD measurement. When CuKα rays are used as the light source for XRD measurement, λ is 0.15418 nm.
[0056] The "BET specific surface area" is a value obtained by a BET one-point method using nitrogen (N2) as the adsorbed substance in accordance with JIS R 1626-1996.
[0057] "Particle size based on volume distribution" refers to the particle size of the powder obtained by volume particle size distribution measurement based on laser diffraction. The particle size obtained by laser diffraction is a diameter approximated by a non-spherical shape. As conditions for volume particle size distribution measurement, the following conditions can be cited.
[0058] Measurement sample: powder slurry
[0059] Refractive index of zirconium oxide: 2.17
[0060] Refractive index of solvent (water): 1.333
[0061] Measuring time: 30 seconds
[0062] Pretreatment: Ultrasonic dispersion treatment
[0063] The “median particle size” refers to a particle size corresponding to a volume ratio of 50% in a cumulative volume particle size distribution curve obtained by volume particle size distribution measurement based on a laser diffraction method.
[0064] The “particle size distribution curve” is a curve showing the particle size distribution of a powder obtained by volume particle size distribution measurement based on a laser diffraction method.
[0065] The “fracture toughness value” is a value of fracture toughness (MPa·m0.5 ). The fracture toughness value is measured using a columnar sintered body sample with a support distance of 30 mm, a width of 4 mm, and a thickness of 3 mm, and the average value of 10 measurements is used as the fracture toughness value of the sintered body of the present embodiment. It should be noted that in JIS R 1607, two fracture toughness measurements, the IF method and the SEPB method, are specified. The IF method tends to measure larger values than the SEPB method. Furthermore, since the IF method is a simple measurement method, the deviation of the measured value of each measurement is large. Therefore, the fracture toughness value in the present embodiment cannot be compared with the fracture toughness value measured by the IF method in terms of absolute value. Similarly, the fracture toughness value measured by methods other than the SEPB method and the fracture toughness value measured by the SEPB method cannot be compared in terms of absolute value.
[0066] The "bending strength" is a value of three-point bending strength obtained by a three-point bending test based on JIS R 1601. The bending strength is measured using a columnar sintered body sample with a support distance of 30 mm, a width of 4 mm, and a thickness of 3 mm, and the average value of 10 measurements is used as the bending strength of the sintered body of the present embodiment.
[0067] "Total light transmittance" refers to the total light transmittance of light with a wavelength of 600nm when the sample thickness is 1.0mm, and can be measured by a method based on JIS K 7361. It is possible to use light with a wavelength of 600nm as incident light, and find the value of the transmittance after the diffuse transmittance and linear transmittance of the incident light are combined. A sample with a thickness of 1mm and a surface roughness (Ra) ≤ 0.04μm on both sides (the measurement surface and the opposite side of the measurement surface), preferably (Ra) ≤ 0.02μm, is used as a measurement sample. A general spectrophotometer (e.g., V-650, manufactured by JASCO Corporation) is used to irradiate the sample with light of a wavelength of 600nm, and the transmitted light is focused by an integrating sphere, thereby measuring the transmittance (diffuse transmittance and linear transmittance) of the sample, and using it as the total light transmittance. As the measurement conditions of the total light transmittance, the following conditions can be cited.
[0068] Bandwidth: 5.0nm
[0069] Data acquisition interval: 0.5nm
[0070] Scanning speed: 1000nm / min
[0071] “Relative density” is the ratio (%) of the measured density to the theoretical density. The measured density of a molded body is the ratio (g / cm 3 ), the measured density of the sintered body is the ratio of the volume measured by the Archimedean method to the mass measured by mass measurement (g / cm3 The theoretical density is the density (g / cm2) obtained from the following equations (6) to (9): 3 ).
[0072] A=0.5080+0.06980X / (100+X) (6)
[0073] C=0.5195-0.06180X / (100+X) (7)
[0074] ρ Z =[124.25(100-X)+225.81X] / [150.5(100+X)A 2 C] (8)
[0075] ρ0=100 / [(Y A / 3.987)+(Y G / 3.637)+(Y S / 2.2)+(100-Y A -Y G -Y S ) / ρ Z ] (9)
[0076] In equations (6) to (9), ρ0 is the theoretical density, ρ Z is the theoretical density of zirconium oxide, A and C are constants, X is the molar ratio (mol%) of the stabilizer (e.g., yttrium oxide) to the total value of zirconium oxide (ZrO2) and the stabilizer (e.g., yttrium oxide (Y2O3)), and Y A , Y G and Y S It is the mass ratio (mass %) of zirconium oxide converted to Al2O3, germanium dioxide converted to GeO2 and silicon dioxide converted to SiO2 relative to the zirconium oxide, stabilizer (for example, yttrium oxide), aluminum oxide, germanium dioxide and silicon dioxide of the molded or sintered body converted to ZrO2, the stabilizer converted to oxide (for example, Y2O3), the total value of Al2O3, GeO2 and SiO2, aluminum oxide converted to Al2O3, germanium dioxide converted to GeO2 and silicon dioxide converted to SiO2.
[0077] Hereinafter, the sintered body according to the present embodiment will be described.
[0078] The present embodiment provides a sintered body, comprising zirconium oxide containing a stabilizer, the monoclinic fraction of the sintered body being greater than 0.5%, and in particular provides the following sintered body: comprising zirconium oxide containing a stabilizer, the monoclinic fraction of the sintered body being greater than 0.5%, and the three-point bending strength determined by a three-point bending test based on JIS R 1601 being greater than 1450 MPa.
[0079] The sintered body of the present embodiment is a sintered body including zirconium oxide containing a stabilizer, and is a sintered body having zirconium oxide containing a stabilizer as a main phase, that is, a so-called zirconium oxide sintered body.
[0080] The stabilizer is a component having the function of stabilizing zirconium oxide, and may be one or more selected from calcium oxide (CaO), magnesium oxide (MgO), cerium oxide (CeO2) and yttrium oxide (Y2O3), preferably at least one of cerium oxide and yttrium oxide, and more preferably yttrium oxide. In the sintered body of the present embodiment, the content of the stabilizer may be an amount sufficient to partially stabilize the zirconium oxide. As the content of the stabilizer, for example, when the stabilizer is yttrium oxide, the molar ratio of yttrium oxide relative to the total value of zirconium oxide (ZrO2) and yttrium oxide (Y2O3) in the sintered body (= {Y2O3 / (ZrO2+Y2O3)}×100 [mol%] (hereinafter also referred to as “yttrium oxide content”) can be exemplified as 1.0 mol% to 2.5 mol%, more preferably 1.1 mol% to 2.2 mol%, further preferably 1.1 mol% to 2.0 mol%, preferably 1.2 mol% to 2.5 mol%. The yttrium oxide content is preferably 1.4 mol% to 2.1 mol%, more preferably 1.5 mol% to 1.8 mol%. In addition, the yttrium oxide content is 1.0 mol% to 1.3 mol% or 1.6 mol%, and in addition, 2.3 mol% to 1.9 mol%, 1.8 mol% to 1.7 mol% or less can be mentioned.
[0081] The stabilizer is preferably dissolved in zirconium oxide, and the sintered body of the present embodiment preferably does not contain undissolved stabilizer, that is, the stabilizer is completely dissolved in zirconium oxide, and more preferably, the XRD pattern of the sintered body of the present embodiment does not have an XRD peak of the stabilizer. In the present embodiment, as an XRD peak different from the XRD peak of zirconium oxide, it can be considered that undissolved stabilizer is included in the case where the XRD peak of the stabilizer can be confirmed. As another embodiment, a method of containing undissolved stabilizer to the extent that the XRD peak of the stabilizer cannot be confirmed can be included in the sintered body of the present embodiment.
[0082] The sintered body of the present embodiment may contain one or more additives selected from aluminum oxide (Al2O3), germanium dioxide (GeO2) and silicon dioxide (SiO2). The additive is preferably at least one of aluminum oxide and germanium dioxide, and more preferably aluminum oxide. By containing the additive, the grain boundary strength between the grains is likely to be high even when the content of the stabilizer of zirconium oxide is small. In the case of including the additive, the sintered body of the present embodiment is a sintered body containing the additive and the balance is zirconium oxide containing the stabilizer. The content of the additive (hereinafter also referred to as "the content of the additive", and in the case where the additive is aluminum oxide, etc., it is also referred to as "the content of aluminum oxide", etc.) is the mass ratio of the additive relative to the total mass of the stabilizer such as zirconium oxide, yttrium oxide and the additive of the sintered body. For example, the content of aluminum oxide in a sintered body containing aluminum oxide as an additive and the balance being zirconium oxide containing yttrium oxide is obtained as ({Al2O3 / (ZrO2+Y2O3+Al2O3)}×100[mass %]). The content of added components can be listed as more than 0.05 mass % and less than 30 mass %, preferably greater than 0.1 mass % and less than 25 mass %, more preferably more than 0.2 mass % and less than 20 mass %. If the content of added components is more than 0.02 mass % and less than 0.3 mass %, there is a tendency that mechanical strength becomes higher, it is difficult to produce a tendency of phase transition to monoclinic zirconia. As preferred content of added components, more than 0 mass %, greater than 0 mass %, more than 0.02 mass %, more than 0.1 mass % or more than 0.3 mass %, and less than 25 mass %, less than 21 mass %, less than 11 mass %, less than 6 mass %, less than 2 mass % or less than 1 mass %.
[0083] The sintered body of the present embodiment preferably does not contain any substance other than inevitable impurities. As an inevitable impurity, hafnium oxide (HfO2) can be exemplified. It should be noted that in the calculation of the values related to the composition such as the theoretical density, the content of stabilizers, and the added components in the present embodiment, hafnium oxide (HfO2) as an inevitable impurity can be calculated as zirconium oxide (ZrO2).
[0084] The monoclinic rate of the sintered body of the present embodiment is 0.5% or more, preferably 0.5% or more and 15% or less, and more preferably 0.8% or more and 12% or less. Since there is a tendency for the fracture toughness to increase, the monoclinic rate is preferably any one of 1% or more and 15% or less, 2% or more and 14% or less, 5% or more and 12% or less, and 7% or more and 11% or less. On the other hand, since there is a tendency for the bending strength to increase, the monoclinic rate is preferably 0.5% or more and 5% or less, and more preferably 0.8% or more and 3% or less.
[0085] The surface of the sintered body just after sintering (as-sintered-surface; hereinafter also referred to as "sintered skin surface") contains more sources of fracture such as roughness and bumps. As the sintered skin surface, for example, a surface with Ra>0.04μm can be listed, and from another point of view, a surface without grinding marks can be listed. In order to prevent the sintered body from being damaged, the sintered skin surface of the sintered body is removed by grinding and other processing before being used for evaluation or various purposes. As a result, the sintered body is in a state where a mirror-like surface (polished-surface; hereinafter also referred to as "mirror surface") is exposed. The mirror surface is a smooth surface, and a surface with Ra≤0.04μm can be exemplified. The monoclinic ratio is the value in the mirror surface of the sintered body, that is, the value of the surface of the mirror sintered body. The existing sintered body with partially stabilized zirconia as the main phase, after mirror processing such as processing and grinding, its crystal phase is composed of at least any one of tetragonal zirconia and cubic zirconia. Therefore, the existing mirror-surface sintered body does not substantially contain monoclinic zirconia, or contains little monoclinic zirconia. On the other hand, a sintered body with low mechanical properties is destroyed during mirror processing, and the measurement sample cannot be processed, and it may be a sintered body that cannot measure the monoclinic rate. In contrast, the sintered body of the present embodiment is a sintered body that can be processed into a mirror-surface sintered body, and the monoclinic rate in the mirror surface can be measured. Furthermore, the mirror surface contains monoclinic zirconia that satisfies the above-mentioned monoclinic rate. Therefore, the sintered body of the present embodiment is considered to be a sintered body having monoclinic zirconia in the entire sintered body, or a sintered body containing tetragonal zirconia that easily undergoes phase transformation to monoclinic zirconia, and can be considered to be different from the existing sintered body having monoclinic zirconia only on the processed surface.
[0086] In the sintered body of the present embodiment, the zirconium oxide includes monoclinic zirconium oxide and at least one of tetragonal zirconium oxide and cubic zirconium oxide, and is preferably composed of monoclinic zirconium oxide and tetragonal zirconium oxide.
[0087] The monoclinic zirconia contained in the sintered body of the present embodiment is a monoclinic zirconia having at least an XRD peak corresponding to the monoclinic zirconia (111) surface in its XRD pattern. In the state before the degradation treatment is implemented, by containing such a monoclinic zirconia, the sintered body easily shows a high fracture toughness value. In addition, there is a tendency for the sintered body to be difficult to hydrothermally degrade. In the case of generating monoclinic zirconia due to the degradation of the sintered body, the intensity of the XRD peak mainly corresponding to the monoclinic zirconia (11-1) surface in the XRD pattern becomes stronger. In contrast, the monoclinic zirconia contained in the sintered body of the present embodiment preferably has at least an XRD peak corresponding to the monoclinic zirconia (111) surface in its XRD pattern, and its monoclinic intensity ratio is preferably more than 0, more than 0.3, more than 0.4, or more than 0.5. The monoclinic intensity ratio is preferably less than 10, less than 8, less than 5, less than 3 or less than 1.5, and can be listed as less than 1.2, and further less than 1.0. In this embodiment, the monoclinic intensity ratio is calculated by formula (3). m In a sintered body having (111) of zero, i.e., a sintered body having no XRD peak corresponding to the (111) plane of monoclinic zirconia, the monoclinic intensity ratio becomes infinite and its value cannot be obtained. That is, the sintered body of the present embodiment preferably does not include a sintered body having an infinite monoclinic intensity ratio.
[0088] The average grain size of the zirconium oxide grains of the sintered body of the present embodiment varies depending on the sintering temperature, and may be, for example, any one of 0.1 μm to 0.8 μm, 0.15 μm to 0.60 μm, 0.20 μm to 0.55 μm, or 0.25 μm to 0.45 μm. In the present embodiment, since the sintered body has a particularly high bending strength, the average grain size is 0.40 μm to 0.50 μm or more, and may be 0.65 μm to 0.60 μm or less.
[0089] The relative density of the sintered body of the present embodiment (hereinafter also referred to as “sintered body density”) is greater than or equal to 98% and less than or equal to 100%, more preferably greater than or equal to 98.4% and less than or equal to 100%, further preferably greater than or equal to 99% and less than or equal to 100%, further preferably greater than or equal to 99.5% and less than or equal to 100%, further preferably greater than or equal to 99.7% and less than or equal to 100%.
[0090] Furthermore, the sintered body of the present embodiment is preferably a sintered body obtained by pressure sintering, and more preferably a sintered body obtained by hot isostatic pressing (hereinafter also referred to as "HIP") (so-called HIP-treated body). The HIP-treated body may be a state in which other sintering methods are used after pressure sintering, for example, a state in which HIP treatment such as normal pressure sintering after pressure sintering is followed by sintering in an oxidizing atmosphere.
[0091] The sintered body of this embodiment preferably has an offset value (hereinafter also referred to as "offset value") of 0.15° or more, 0.3° or more, or 0.6° or more of the tetragonal zirconia (113) plane. Alternatively, the offset value may be 2.0° or less, 1.5° or less, or 1.0° or less.
[0092] The offset value is the difference in 2θ of the tetragonal zirconia (113) plane when the tilt angle ψ = 0° and ψ = 45°, and is particularly the difference in 2θ of the tetragonal zirconia (113) plane when the tilt angle ψ = 0° and ψ = 45° obtained by powder X-ray diffraction measurement using CrKα rays as a radiation source. When the offset value is obtained in the present embodiment, the following conditions can be cited as conditions for powder X-ray diffraction measurement.
[0093] Radiation source: CrKα ray (λ=2.29100nm)
[0094] Accelerating voltage: 30 kV
[0095] Current: 30mA
[0096] Measurement method: Same inclination method
[0097] Collimator diameter: 4mm
[0098] Measuring lattice plane: tetragonal zirconium oxide (113) plane
[0099] Tilt angle ψ: 0° and 45°
[0100] Such powder X-ray diffraction measurement can be performed using a general apparatus (for example, Auto MATE, manufactured by Rigaku Corporation).
[0101] In the above measurement, the peak corresponding to the tetragonal zirconia (113) plane was confirmed as a peak having a peak top at 2θ = 152 ± 2.0°. The offset value is the 2θ (hereinafter also referred to as “2θ”) of the peak top corresponding to the tetragonal zirconia (113) plane at an inclination angle ψ = 0° as shown in the following formula: (0°) ”) and the 2θ of the peak top corresponding to the tetragonal zirconia (113) plane when the inclination angle ψ=45° (hereinafter also referred to as “2θ (45°) ”) is the value obtained by the difference between
[0102] Offset value (°) = 2θ (45°) -2θ (0°)
[0103] It is believed that, according to the crystal state showing such a shift value, stress between grains is more likely to be generated than in the conventional sintered body. Therefore, the sintered body of the present embodiment has a higher fracture toughness value, and further, for example, in the case of a sintered body containing yttrium oxide as a stabilizer, it is believed that even when the yttrium oxide content is 2.0 mol% or less, less than 1.9 mol%, 1.8 mol% or less, or 1.7 mol% or less, defects are less likely to occur, and a sintered body having a higher fracture toughness value can be obtained.
[0104] The sintered body of the present embodiment can be exemplified by a fracture toughness value (fracture toughness value measured by a method based on the SEPB method specified in JIS R 1607) of 6 MPa·m 0.5 Above and 11MPa·m 0.5 Below, preferably 6.2 MPa·m 0.5 More preferably, 7 MPa·m 0.5 More preferably, 7.2 MPa·m 0.5 More preferably, 8 MPa·m 0.5 Above, particularly preferably 8.5 MPa·m 0.5 The fracture toughness value is preferably high, for example, 11 MPa·m 0.5 Below, further 10.5MPa·m 0.5 Below, more preferably 9.5 MPa·m 0.5 Below, further 9MPa·m 0.5 Below, more preferably 8.8 MPa·m 0.5 By having such a fracture toughness value, it is easy to process the sintered body into a sintered body with a thickness of 1 mm or less, and further, a sintered body with a thickness of 0.5 mm or less. Therefore, the sintered body of the present embodiment can also be formed into a sintered body with a thickness of 0.05 mm or more and 0.3 mm or less, and further, a sintered body with a thickness of 0.08 mm or more and 0.25 mm or less.
[0105] The bending strength of the sintered body of the present embodiment is greater than 1450 MPa, further greater than 1455 MPa, further greater than 1550 MPa, and further greater than 1580 MPa. Preferred bending strengths include greater than 1450 MPa and less than 2300 MPa, further preferably greater than 1500 MPa and less than 2200 MPa, and more preferably greater than 1550 MPa and less than 2150 MPa.
[0106] It is known that it is difficult to improve the fracture toughness value of a sintered body with high bending strength. For example, the fracture toughness value of a sintered body with a bending strength of 1400 MPa or more is less than 7.0 MPa·m0.5 In contrast, the sintered body of the present embodiment has high mechanical strength and has an improved fracture toughness value compared to conventional sintered bodies. Therefore, as a preferred sintered body of the present embodiment, a sintered body having a bending strength greater than 1450 MPa and a fracture toughness of 7.0 MPa·m 0.5 Above, 7.5MPa·m 0.5 Above or 8.0MPa·m 0.5 The upper limits of the bending strength and fracture toughness of such a sintered body may also be the same as the above values.
[0107] Therefore, the sintered body of the present embodiment is preferably a sintered body comprising zirconium oxide containing a stabilizer, having a monoclinic crystal ratio of 0.5% or more, and having a three-point bending strength of more than 1450 MPa as determined by a three-point bending test in accordance with JIS R 1601, and having a fracture toughness of 7 MPa·m as measured by a method in accordance with the SEPB method specified in JIS R 1607. 0.5 Above and 11MPa·m 0.5 the following.
[0108] The sintered body of the present embodiment has a bending strength of more than 1450 MPa, 1455 MPa or more, 1490 MPa or more, or 1500 MPa or more, and preferably is 2300 MPa or less, 2200 MPa or less, 2150 MPa or less, 2100 MPa or less, 2000 MPa or less, or 1990 MPa or less, and a fracture toughness value of 6.0 MPa·m 0.5 Above, 6.5MPa·m 0.5 Above, 7.0MPa·m 0.5 Above or 7.5MPa·m 0.5 Above, and 11MPa·m 0.5 Below, 10.5MPa·m 0.5 Below, 10MPa·m 0.5 Below, 9.5MPa·m 0.5 Below or 9.0MPa·m 0.5 the following.
[0109] The total light transmittance of the sintered body of the present embodiment is preferably 20% to 50%, more preferably 25% to 45%, and still more preferably 30% to 40%. In particular, when the amount of the added component is greater than 0% to 25% to 5%, further 0.2% to 5%, and further 0.23% to 3%, the total light transmittance is 25% to 45%, and further 35% to 40%.
[0110] The tetragonal zirconia contained in the sintered body of the present embodiment is preferably difficult to undergo phase transformation to monoclinic zirconia due to hydrothermal treatment (hereinafter also referred to as "hydrothermal degradation"). The ratio of the tetragonal crystal rate of the sintered body of the present embodiment after immersion treatment in hot water at 140°C for 6 hours to the tetragonal crystal rate before immersion treatment in hot water at 140°C for 6 hours (hereinafter also referred to as "residual tetragonal crystal rate" or "△T%") is preferably 15% or more, more preferably 70% or more, and further preferably 80% or more. By immersion treatment in hot water at 140°C for 6 hours, when the tetragonal zirconia is not transformed into monoclinic zirconia, the residual tetragonal crystal rate is 100%, so the residual tetragonal crystal rate of the sintered body of the present embodiment is less than 100%, and further preferably less than 95%.
[0111] The higher the content of the additive, the more it tends to suppress hydrothermal degradation. In the sintered body of the present embodiment, when the content of the additive is 0 mass%, that is, when no additive is included, the residual tetragonal rate can be exemplified as 15% or more and 100% or less, preferably 20% or more and 100% or less, and more preferably 50% or more and 80% or less. The sintered body of the present embodiment contains an additive, and when the content of the additive is greater than 0 mass% and less than 5 mass%, the residual tetragonal rate can be exemplified as 65% or more and 100% or less, and preferably 70% or more and 90% or less. The sintered body of the present embodiment contains an additive, and when the content of the additive is greater than 5 mass% and less than 30 mass%, the residual tetragonal rate can be exemplified as 70% or more and 100% or less, and preferably 76% or more and 95% or less.
[0112] The shape of the sintered body of this embodiment can be any desired shape, and in addition to basic shapes such as cube, rectangular parallelepiped, polygon, plate, disk, column, cone, sphere, and roughly spherical, it can be any shape of parts corresponding to various uses.
[0113] The manufacturing method of the sintered body of the present embodiment is arbitrary, but a manufacturing method including the following steps can be listed: a step of sintering a powder as a raw material, which contains zirconium oxide with a monoclinic crystal ratio greater than 70% and a crystallite diameter greater than 23nm and less than 80nm, to make a pre-sintered body with a relative density of less than 99%; and a step of pressure sintering the pre-sintered body. Furthermore, a manufacturing method including the following steps can be listed: a pre-sintering step of pre-sintering a molded body containing zirconium oxide with a monoclinic crystal ratio greater than 70% and a crystallite diameter greater than 23nm and less than 80nm, to make a pre-sintered body with a relative density of less than 99%; and a pressure sintering step of pressure sintering the pre-sintered body. In addition, in the manufacturing method of the sintered body of the present embodiment, at least one of calcination and processing can be performed on the molded body before and after the pre-sintering as needed.
[0114] The powder used for pre-sintering is preferably in a state after molding, that is, a molded body (compressed powder body). The molding can be performed by a known method, such as at least one selected from uniaxial pressing, cold isostatic pressing, slide casting and injection molding, preferably at least one selected from uniaxial pressing, cold isostatic pressing and injection molding. Thus, a molded body, that is, a compressed powder body formed by physically agglomerated powder particles, is obtained.
[0115] In the case where the molded body is processed before sintering, the molded body can also be calcined as needed to form a calcined body. The calcined body in the present embodiment is composed of molten particles, and the particles of zirconium oxide are in a state of necking each other. In order to make a calcined body composed of molten particles, calcination only requires heat treatment of the powder, preferably the molded body, in a manner lower than the sintering temperature. For example, the heat treatment can be performed in an atmospheric atmosphere at a temperature of 800°C or more and less than 1200°C, preferably 900°C or more and less than 1150°C, more preferably 900°C or more and less than 1100°C, and further preferably 950°C or more and less than 1100°C. Thus, a calcined body composed of molten particles is obtained. The calcined body can also be processed into any shape before pre-sintering.
[0116] Sintering can be performed by a known method, for example, one or more methods selected from pressure sintering, vacuum sintering and normal pressure sintering. Normal pressure sintering is preferably used for sintering of a powder, preferably a molded body. On the other hand, pressure sintering is preferably used for sintering of a pre-sintered body, and at least one of hot pressing and HIP treatment is preferably used, and HIP treatment is more preferably used.
[0117] In pressure sintering, a pre-sintered body having a relative density of 99% or less, preferably 95% or more and 99% or less, and more preferably 97% or more and less than 99% is provided. The pre-sintered body can be obtained by any sintering method, but it is sufficient as long as the molded body (or calcined body) is sintered at normal pressure. If the relative density of the pre-sintered body is set to this range, it is easy to eliminate the pores of the sintered body during pressure sintering. In order to make the relative density of the pre-sintered body within the above range, it can be illustrated that the pre-sintering is performed in an atmospheric atmosphere, at a temperature of 1100°C or more and 1400°C or less, preferably at a temperature of 1100°C or more and 1400°C or less, and more preferably at a temperature of 1150°C or more and 1400°C or less. In the present embodiment, normal pressure sintering refers to a method of sintering by heating without applying an external force to the sintered object during sintering.
[0118] The pressure sintering can be performed by treating the pre-sintered body at a treatment pressure of 50 MPa or more and a treatment temperature of 1200°C or more. As a preferred pressure sintering, HIP treatment can be performed for 0.5 to 2 hours at a treatment temperature of 50 MPa or more and 500 MPa or less and 1200°C or more and 1550°C or less in any atmosphere of a reducing atmosphere and an inert atmosphere. A HIP treated body is obtained by the HIP treatment. As the above-mentioned atmosphere, at least one atmosphere of nitrogen and argon, and an argon atmosphere can be mentioned.
[0119] If necessary, the HIP-treated body or other pressurized body may be heat-treated in an oxidizing atmosphere. Examples of heat-treatment conditions include an air atmosphere, 900° C. to 1100° C., and 0.5 to 5 hours.
[0120] The HIP-processed body or the HIP-processed body after heat treatment in an oxidizing atmosphere may be used as the sintered body of the present embodiment.
[0121] The sintered body of the present embodiment can be used as a component including the sintered body of zirconium oxide, and is suitable for components for pulverizers, precision machinery components, structural materials such as optical connector components, biological materials such as dental materials, decorative components, and exterior materials such as exterior components of electronic devices.
[0122] Hereinafter, the powder for the sintered body according to the present embodiment will be described.
[0123] The powder for sintered body of the present embodiment (hereinafter also referred to as "powder of the present embodiment") is a powder comprising zirconium oxide containing a stabilizer and having a monoclinic fraction of greater than 70%, wherein the crystallite diameter of the monoclinic zirconium oxide is greater than 23 nm and less than 80 nm.
[0124] The powder of the present embodiment contains zirconium oxide containing a stabilizer and having a monoclinic crystal ratio of more than 70%. That is, the powder of the present embodiment mainly contains zirconium oxide containing a stabilizer composed of monoclinic zirconium oxide. In the case of zirconium oxide powder without a stabilizer, even if it is sintered, it is difficult to obtain a sintered body containing tetragonal zirconium oxide, which is the main reason for the fracture toughness. The powder of the present embodiment is a so-called zirconium oxide powder mainly composed of zirconium oxide.
[0125] The stabilizer may be selected from calcium oxide (CaO), magnesium oxide (MgO), cerium oxide (CeO2) and yttrium oxide (Y2O3) at least one, preferably at least any one of cerium oxide and yttrium oxide, more preferably yttrium oxide. In the case where the stabilizer is yttrium oxide, the molar ratio of yttrium oxide (yttrium oxide content) relative to the total value of zirconium oxide (ZrO2) and yttrium oxide (Y2O3) in the powder can be exemplified as 1.0 mol% or more and 2.5 mol% or less, more preferably 1.1 mol% or more and 2.0 mol% or less, preferably 1.2 mol% or more and less than 2.0 mol%, more preferably 1.2 mol% or more and 1.8 mol% or less. In a powder comprising zirconium oxide containing yttria and having a monoclinic fraction greater than 70%, and the crystallite diameter of the monoclinic zirconium oxide is greater than 23 nm and less than 80 nm, it is particularly preferred that its content is greater than 1.0 mol%, greater than 1.1 mol%, greater than 1.2 mol% or greater than 1.4 mol%, and less than 2.0 mol%, less than 2.0 mol%, less than 1.8 mol% or less than 1.7 mol%.
[0126] The stabilizer is preferably dissolved in zirconium oxide, and the powder of the present embodiment preferably does not contain undissolved stabilizer, and more preferably does not have an XRD peak of the stabilizer in the XRD pattern of the powder.
[0127] As the main crystal phases of zirconium oxide, monoclinic zirconium oxide, tetragonal zirconium oxide and cubic zirconium oxide are known. The zirconium oxide in the powder of the present embodiment includes monoclinic zirconium oxide, preferably includes at least any one of monoclinic zirconium oxide, tetragonal zirconium oxide and cubic zirconium oxide, and more preferably includes monoclinic zirconium oxide and tetragonal zirconium oxide.
[0128] The monoclinic rate of zirconium oxide is greater than 70%, preferably greater than 80%, and more preferably greater than 85%. The monoclinic rate is less than 100%, and when the zirconium oxide contains at least one of tetragonal zirconium oxide and cubic zirconium oxide, the monoclinic rate is less than 100%. In addition, the tetragonal rate is preferably less than 30%, more preferably less than 20%, preferably less than 15%, and may be less than 10%, and more preferably less than 7%. When the zirconium oxide does not contain tetragonal zirconium oxide, the tetragonal rate is 0%, and the tetragonal rate may be greater than 0%.
[0129] The crystallite diameter of monoclinic zirconia (D m ) is greater than 23 nm and less than 80 nm, more preferably greater than 30 nm and less than 60 nm, and further preferably greater than 35 nm and less than 55 nm. In another embodiment, the crystallite diameter (D m ) is listed as being greater than 30 nm and less than 50 nm, more preferably being greater than 35 nm and less than 50 nm, and may also be greater than 35 nm and less than 45 nm, and further being greater than 36 nm and less than 40 nm.
[0130] The powder of this embodiment may contain one or more additives selected from aluminum oxide (Al2O3), germanium dioxide (GeO2) and silicon dioxide (SiO2). The additive is preferably at least one of aluminum oxide and germanium dioxide, and more preferably aluminum oxide. By containing the additive, even when the content of the stabilizer of zirconium oxide is small, defects such as cracks during sintering are not easy to occur, and the yield during sintering is not easy to decrease. Regarding the content of the additive, the mass ratio of the additive relative to the total mass of stabilizers such as zirconium oxide and yttrium oxide and the additive of the powder can be 0.05 mass% or more and 30 mass% or less, preferably greater than 0.1 mass% and less than 25 mass%, more preferably 0.2 mass% or more and less than 20 mass%, and further preferably 0.23 mass% or more and less than 6 mass%.
[0131] The powder of this embodiment preferably contains no impurities, and for example, the phosphorus (P) content can be 0.1 mass % or less and less than 0.1 mass %, respectively. On the other hand, it may contain inevitable impurities such as hafnium oxide (HfO 2 ) of zirconium oxide.
[0132] The powder of this embodiment can be exemplified by a BET specific surface area of 6 m 2 / g or more and less than 20m 2 / g. The BET specific surface area is 6m 2 / g or more, it is easy to sinter at a relatively low temperature. 2 / g, there is a tendency that the physical aggregation of the powder is suppressed. In order to more easily obtain these effects, the BET specific surface area is preferably 8m 2 / g or more and 18m 2 / g or less, more preferably 10m 2 / g or more and 17m 2 / g or less, more preferably 10m 2 / g or more and 15m 2 / g or less, and more preferably greater than 10m 2 / g and 15m 2On the other hand, sintering is easily promoted in a lower temperature range, so the BET specific surface area is 14 m 2 / g or above or 16m 2 / g or more, and preferably 18m 2 / g or less.
[0133] The median particle size of the powder of the present embodiment is preferably 0.05 μm or more and 0.3 μm or less, and more preferably 0.1 μm or more and 0.2 μm or less.
[0134] The powder of this embodiment can exemplify a multimodal distribution of the volume particle size distribution curve, preferably a distribution of a peak having a particle size of at least 0.05 μm and 0.2 μm or less and a particle size greater than 0.2 μm and 0.5 μm or less, and more preferably a distribution of a peak having a particle size of 0.05 μm or more and 0.2 μm or less and a particle size of 0.3 μm or more and 0.5 μm or less (extreme value). The filling property of a powder having a multimodal distribution such as a bimodal distribution tends to increase during molding. Since the density of the obtained molded body tends to increase, the ratio of the peak having a particle size of 0.3 μm or more and 0.5 μm or less to the peak having a particle size of 0.05 μm or more and 0.2 μm or less in the volume particle size distribution curve (hereinafter, also referred to as "particle size peak ratio") is preferably greater than 0 and less than 1, more preferably 0.1 or more and 0.9 or less, and more preferably 0.2 or more and 0.8 or less.
[0135] The powder of the present embodiment preferably has high moldability. When the powder of the present embodiment is subjected to uniaxial press molding at a pressure of 70±5 MPa and then processed by cold isostatic pressing (hereinafter also referred to as "CIP") at a pressure of 196±5 MPa to form a molded body, the relative density of the molded body (hereinafter also referred to as "molded body density") is preferably greater than 49% and less than 56%, and more preferably greater than 50% and less than 54%.
[0136] The powder of the present embodiment may contain a resin for improving fluidity, or may be a composition containing the powder of the present embodiment and a resin (hereinafter also referred to as a "composite"). The resin contained in the composite can be any known resin used in ceramic compositions, for example, thermoplastic resins. As preferred resins, any one or more of the group consisting of acrylic resins, polystyrene, and polyalkyl carbonates can be exemplified, preferably acrylic resins.
[0137] The content of the powder in the composite can be exemplified by a mass ratio of the powder relative to the mass of the composite, such as 50% to 97%, 70% to 95%, 80% to 90%, etc. The content of the powder in the composite can be obtained by the mass ratio of the composite after the resin is removed relative to the mass of the composite. The method for removing the resin is arbitrary, and examples thereof include heat treatment in an air atmosphere or at least 200° C. and at most 500° C.
[0138] In addition to the resin, the composite may also contain wax and other ingredients as additives. By containing these ingredients, additional effects such as good demoulding properties of the molding die can be obtained. As ingredients such as wax, one or more selected from polyethylene, polypropylene, polyacrylonitrile, acrylonitrile-styrene copolymer, ethylene-vinyl acetate copolymer, styrene-butadiene copolymer, polyacetal resin, petroleum wax, synthetic wax, vegetable wax, stearic acid, phthalate plasticizer and adipic acid ester can be exemplified.
[0139] The powder of this embodiment can be used as a precursor of a calcined body or a sintered body, and is suitable as a raw material powder for structural materials such as pulverizer parts, precision machinery parts, optical connector parts, biological materials such as dental materials, decorative parts, and exterior materials such as electronic device exterior parts.
[0140] When the powder of the present embodiment is made into a sintered body or the like, the powder may be compacted and then fired or sintered by a known method.
[0141] When the powder of the present embodiment is used as a molded body, the molding can be performed by a known method, such as at least one selected from the group consisting of uniaxial pressing, cold isostatic pressing, slide casting and injection molding. When a resin such as a composite is used to make the molded body, the obtained molded body can also be heat-treated to remove the resin as needed. As heat treatment conditions, an atmospheric atmosphere, 400°C or more and less than 800°C can be exemplified.
[0142] The molded body may also be calcined as required. The calcination can be performed at a temperature lower than the sintering temperature of the powder, for example, in an air atmosphere at 800°C or higher and lower than 1200°C, preferably 900°C or higher and lower than 1150°C, more preferably 900°C or higher and lower than 1100°C, and further preferably 950°C or higher and lower than 1100°C. Thus, the powder particles are initially sintered to form molten particles with a neck, thereby obtaining a calcined body.
[0143] Sintering can be performed by a known method, for example, one or more selected from pressure sintering, vacuum sintering and pressureless sintering, preferably including at least pressure sintering. In the case of pressure sintering, it can be illustrated as follows: the above-mentioned zirconium oxide powder is molded, calcined as needed, pre-sintered in an atmospheric atmosphere, 1100°C or more and 1400°C or less, preferably greater than 1100°C and 1400°C or less, more preferably 1150°C or more and 1400°C or less, and the obtained pre-sintered body is subjected to HIP treatment for 0.5 to 2 hours under an argon atmosphere, at a treatment temperature of 50MPa or more and 500MPa or less, 1200°C or more and 1550°C or less. Usually, in pressure sintering, the closed pores of the sintered body can be forcibly eliminated. Therefore, the sintered body (pressureless sintered body) obtained by pressure sintering is densified, and there is a tendency that the mechanical strength of the sintered body is improved. However, even if the pressure-sintered body is subjected to pressure sintering, the fracture toughness value of the sintered body hardly changes. In contrast, by using the powder of this embodiment as a starting material and subjecting it to pressure sintering, preferably HIP treatment, a sintered body having a fracture toughness of 7.0 MPa·m 0.5 Above, and even higher than 7.0MPa·m 0.5 A sintered body with a higher fracture toughness value and a flexural strength of 1400 MPa or more, 1450 MPa or more, or a high toughness greater than 1450 MPa.
[0144] Next, a method for producing the powder according to the present embodiment will be described.
[0145] The powder of the present embodiment may be produced by any method as long as it has the above-mentioned characteristics. A preferred method for producing the powder of the present embodiment includes a method comprising the following steps: a step of heat-treating a composition of a zirconium oxide sol containing zirconium oxide having an average sol particle size of 150 nm to 400 nm and containing monoclinic zirconium oxide, and a stabilizer source at 950° C. to 1250° C. to produce a calcined powder; and a step of crushing the calcined powder.
[0146] A process of preparing a calcined powder (hereinafter also referred to as a "powder calcining process") by heat treating a composition of a zirconia sol containing monoclinic zirconia and a stabilizer source at a temperature between 950°C and 1250°C to obtain a calcined powder which is a precursor of the powder of the present embodiment.
[0147] In the powder calcining step, heat treatment is performed at 950°C or higher and 1250°C or lower, and further at 1000°C or higher and 1250°C or lower. By making the heat treatment at 950°C or higher, a powder that is easily densified in normal pressure sintering is obtained. On the other hand, by making the heat treatment at 1250°C or lower, a powder that is easily dispersed by pulverization is easily obtained. The time of the heat treatment varies depending on the heat treatment temperature, and for example, 30 minutes or higher and 2 hours or lower can be cited.
[0148] The atmosphere for the heat treatment is arbitrary, and can be any one selected from an oxidizing atmosphere, a reducing atmosphere, an inert atmosphere, and a vacuum atmosphere. An oxidizing atmosphere is preferred, and an air atmosphere is more preferred.
[0149] The average sol particle size of the zirconium oxide sol is 150 nm to 400 nm, preferably 180 nm to 400 nm, and more preferably 185 nm to 300 nm. The average sol particle size may be 150 nm to 270 nm, further 150 nm to 200 nm, or 190 nm to 400 nm, further 200 nm to 300 nm.
[0150] The zirconia sol preferably contains zirconia containing monoclinic zirconia and zirconia composed of crystalline zirconia (hereinafter also referred to as "crystalline zirconia sol"), and more preferably contains crystalline zirconia whose main phase is monoclinic zirconia.
[0151] Since the zirconia sol tends to be easily crushed, the zirconium element amount (hereinafter also referred to as "adsorbed zirconium amount") determined by the following formula is preferably 0 mass % to 1 mass %, more preferably 0 mass % to 0.5 mass %, and even more preferably 0 mass % to 0.01 mass %.
[0152] W Zr =(m / m0)×100
[0153] In the above formula, W Zr is the amount of adsorbed zirconium (mass %). m is the mass (mg) of zirconium oxide (ZrO2) converted from the amount of zirconium in the filtrate obtained by ultrafiltration using an ultrafiltration membrane with a molecular weight cutoff of 500 to 3 million. The amount of zirconium in the filtrate can be measured by ICP analysis. m o is the mass (mg) of the zirconium oxide sol before ultrafiltration after heat treatment in air at 1000°C for 1 hour. m and m o The measurement can be performed by preparing the same amount of zirconium oxide sol before ultrafiltration.
[0154] The zirconia sol provided for the powder calcination step may be prepared by any method as long as it has the above-mentioned characteristics. As a method for preparing the zirconia sol, at least one of a hydrothermal synthesis method and a hydrolysis method may be exemplified. In the hydrothermal synthesis method, a coprecipitate obtained by mixing a zirconium salt and an alkali in the presence of a solvent is heat-treated at 100 to 200° C., thereby obtaining the zirconia sol. In addition, in the hydrolysis method, the zirconium salt is heated in the presence of a solvent, and the zirconium salt is hydrolyzed to obtain the zirconia sol. In this way, the zirconia sol may be exemplified by a zirconia sol obtained by a hydrothermal synthesis method or a hydrolysis method, and preferably a zirconia sol obtained by a hydrolysis method.
[0155] The precursor used in the method for producing zirconium oxide sol may be a zirconium salt, which may be one or more selected from zirconium oxychloride, zirconium oxynitrate, zirconium chloride and zirconium sulfate, preferably at least one of zirconium oxynitrate and zirconium oxychloride, and more preferably zirconium oxychloride.
[0156] Hereinafter, a preferred method for producing zirconium oxide sol will be described by taking a hydrolysis method as an example.
[0157] The conditions for the hydrolysis may be any conditions under which the hydrolysis of the zirconium salt is sufficiently carried out, and for example, boiling and refluxing the zirconium salt aqueous solution for 130 hours or more and 200 hours or less. By performing the hydrolysis at an anion concentration in the zirconium salt aqueous solution of 0.2 mol / L or more and 0.6 mol / L or less, and further at 0.3 mol / L or more and 0.6 mol / L or less, there is a tendency for the average sol particle size to become larger.
[0158] As long as the stabilizer source is at least any one of the stabilizer and the compound as its precursor, more than one of the oxide, hydroxide, oxyhydroxide, chloride, acetate, nitrate and sulfate selected from the precursor of the stabilizer can be exemplified, preferably at least any one of chloride and nitrate. The stabilizer source is preferably at least any one of yttrium oxide and the yttrium compound as its precursor. As a preferred stabilizer source (hereinafter, the stabilizer including yttrium oxide, etc. will also be referred to as "yttrium oxide source", etc.), more than one selected from yttrium chloride, yttrium nitrate and yttrium oxide, and then at least any one of yttrium chloride and yttrium oxide can be cited. When the stabilizer source is a yttrium oxide source, the content of the yttrium oxide source in the composition, as a molar ratio of the yttrium oxide source converted as Y2O3 relative to the total value of the values obtained by converting zirconium (Zr) and yttrium (Y) in the composition into ZrO2 and Y2O3, respectively, can be exemplified as 1.0 mol% or more and 2.5 mol% or less, further preferably 1.1 mol% or more and 2.0 mol% or less, preferably 1.2 mol% or more and less than 2.0 mol%, and more preferably 1.2 mol% or more and 1.8 mol% or less.
[0159] The composition to be subjected to the powder calcining step may contain the above-mentioned zirconium oxide sol and a stabilizer source, and all or part of the stabilizer source may be dissolved in the zirconium oxide sol.
[0160] For example, by mixing a zirconium salt and a stabilizer source and hydrolyzing them, or by mixing a zirconium salt, a stabilizer source, and an alkali to form a coprecipitate, at least a portion of the stabilizer source can be easily dissolved in zirconium oxide.
[0161] The composition to be subjected to the powder calcination step may contain one or more additional component sources selected from the group consisting of an alumina source, a germanium dioxide source, and a silica source. The additional component source is preferably at least one of an alumina source and a germanium dioxide source, and is preferably an alumina source.
[0162] The alumina source is at least one of alumina and an aluminum compound serving as a precursor thereof, and may be exemplified by one or more selected from alumina, aluminum hydroxide, aluminum nitrate, and aluminum chloride. Alumina is preferred, and at least one of alumina sol and alumina powder is more preferred.
[0163] The germanium dioxide source is at least one of germanium dioxide and a germanium compound serving as its precursor, and may be exemplified by one or more selected from germanium dioxide, germanium hydroxide and germanium chloride, preferably germanium dioxide, and more preferably at least one of germanium dioxide sol and germanium dioxide powder.
[0164] The silica source is at least one of silica and a silicon compound serving as a precursor thereof, and can be exemplified by one or more selected from silica and tetraethyl orthosilicate, preferably silica, and more preferably at least one of silica powder, silica sol, fumed silica and precipitated silica.
[0165] Regarding the content of the source of the added component, it can be cited that the total ratio of the mass of Al, Ge and Si converted into Al2O3, GeO2 and SiO2, respectively, relative to the total mass of Zr, Y, Al, Ge and Si in the composition converted into ZrO2, Y2O3, and Al2O3, GeO2 and SiO2, is greater than 0.05 mass% and less than 30 mass%, preferably greater than 0.1 mass% and less than 25 mass%, and more preferably greater than 0.2 mass% and less than 20 mass%.
[0166] For example, regarding the content of the alumina source, the ratio of the mass of the alumina source converted into Al2O3 relative to the total mass of Zr, Y and Al in the composition converted into ZrO2, Y2O3 and Al2O3, respectively, is 0.05 mass% or more and 30 mass% or less, preferably greater than 0.1 mass% and less than 25 mass%, and more preferably 0.2 mass% or more and less than 20 mass%.
[0167] In addition, regarding the content of the germanium dioxide source, the ratio of the mass of the germanium dioxide source converted into GeO2 relative to the total mass of Zr, Y and Ge in the composition converted into ZrO2, Y2O3 and GeO2, is 0.05 mass% or more and 30 mass% or less, preferably greater than 0.1 mass% and less than 25 mass%, and more preferably 0.2 mass% or more and less than 20 mass%.
[0168] In addition, regarding the content of the silica source, the ratio of the mass of the silica source converted to SiO2 relative to the total mass of Zr, Y and Si in the composition converted to ZrO2, Y2O3 and SiO2, respectively, can be listed as being greater than 0.05 mass% and less than 30 mass%, preferably greater than 0.1 mass% and less than 25 mass%, and more preferably greater than 0.2 mass% and less than 20 mass%.
[0169] The physical properties of the calcined powder include a BET specific surface area of 3 m 2 / g or more and 15m 2 / g or less, and the crystallite diameter of the monoclinic crystal is from 20 nm to 60 nm.
[0170] In the step of pulverizing the calcined powder (hereinafter also referred to as the "pulverization step"), the calcined powder is pulverized. Zirconia with a low stabilizer content is prone to cracks, gaps, etc. during sintering. In contrast, by pulverizing the calcined powder in the present embodiment, the yield during sintering is likely to be high, and there is a tendency that the obtained sintered body is not easily hydrothermally degraded.
[0171] In order to obtain a powder of the desired composition, in the pulverizing step, the calcined powder and the mixed powder of the alumina source and the additive source may be pulverized instead of the calcined powder. The additive source may be exemplified by the above-mentioned additive source. In the case where the additive source is mixed in the pulverizing step, the content of the additive source is such that the total mass of the mass ratio of Al converted to Al2O3, the mass ratio of Ge converted to GeO2, and the mass ratio of Si converted to SiO2 is 0.05% by mass or more and 30% by mass or less, preferably greater than 0.1% by mass and less than 25% by mass, and more preferably 0.2% by mass or more and less than 20% by mass, relative to the total mass of the mixed powder selected from Zr, Y, Al, Ge, and Si converted to ZrO2, Y2O3, and Al2O3, GeO2, and SiO2, respectively. The additive source and the calcined powder may be mixed in this manner.
[0172] The pulverization method is arbitrary, as long as it is at least any one of wet pulverization and dry pulverization, preferably wet pulverization. As a specific wet pulverization, one or more selected from a ball mill, a vibration mill and a continuous medium stirring mill can be exemplified, preferably a ball mill. As the pulverization conditions using a ball mill, for example, it can be listed as follows: mixing the calcined powder with a solvent to prepare a slurry having a mass ratio of the calcined powder to the mass of the slurry of 30 mass% or more and 60 mass% or less, and the slurry is pulverized for more than 10 hours and less than 100 hours using zirconia balls with a diameter of more than 1 mm and less than 15 mm as a pulverization medium.
[0173] After wet pulverization, the mixture may be dried by any method to obtain a powder. Drying conditions include air atmosphere and 110° C. to 130° C.
[0174] In order to improve the operability of the powder, the method for manufacturing the powder of the present embodiment may also include a step of granulating the powder (hereinafter also referred to as a "granulation step"). Granulation is an arbitrary method, and an example thereof is spray granulation of a slurry obtained by mixing powder and a solvent. The solvent is at least one of water and alcohol, preferably water. The granulated powder (hereinafter also referred to as "powder particles") has an average particle size of 30 μm to 80 μm, more preferably 40 μm to 60 μm, and more preferably 50 μm to 60 μm, and a bulk density of 1.00 g / cm 3 Above and 1.40g / cm 3 Below, further 1.10g / cm 3 Above and 1.30g / cm 3 the following.
[0175] [Example]
[0176] Hereinafter, the present invention will be described using examples, but the present invention is not limited to these examples.
[0177] (Average sol particle size)
[0178] The average sol particle size of the zirconia sol was measured using a dynamic light scattering particle size distribution measuring device (device name: UPA-UT151, manufactured by MicrotracBEL Co., Ltd.) As a pretreatment of the sample, a solution containing hydrated zirconia sol was suspended in pure water and dispersed for 3 minutes using an ultrasonic homogenizer.
[0179] (Monoclinic crystal ratio, tetragonal crystal ratio, D t and D m )
[0180] The XRD pattern of the powder sample was obtained using a general X-ray diffractometer (trade name: Ultima IIV, manufactured by Rigaku Corporation). The conditions for XRD measurement are as follows.
[0181] Radiation source: CuKα radiation (λ = 0.15418nm)
[0182] Measurement mode: continuous scan
[0183] Scanning speed: 4° / min
[0184] Step size: 0.02°
[0185] Measuring range: 2θ=26°~33°
[0186] Using "PRO-FIT" as the obtained XRD pattern and calculation program, the monoclinic ratio, tetragonal ratio, and D t and D m .
[0187] (BET specific surface area)
[0188] The BET specific surface area of the powder sample was measured using a general flow type specific surface area automatic measuring device (device name: FlowSorb III2305, manufactured by Shimadzu Corporation) and nitrogen as adsorption gas by a method based on JIS R 1626-1996. Prior to the measurement, the powder sample was degassed in an air atmosphere at 250° C. for 30 minutes as a pretreatment.
[0189] (Particle size distribution measurement)
[0190] The volume particle size distribution curve of the powder sample was measured by the HRA mode of Microtrac particle size distribution meter (trade name: MT3000II, manufactured by Microtrac BEL Co., Ltd.) to measure the median particle size. Before measurement, the powder sample was suspended in pure water and dispersed for 10 minutes using an ultrasonic homogenizer as a pretreatment.
[0191] (Molding body density)
[0192] The mass of the molded body sample was measured with a balance, and the volume was measured with a vernier caliper, and the density was calculated from the dimensions. The measured density was calculated from the obtained mass and volume. The theoretical density was calculated using equations (6) to (9), and the relative density (%) was calculated from the value of the measured density (ρ) relative to the theoretical density (ρ0) as the density of the molded body.
[0193] (Monoclinic ratio and monoclinic strength ratio of sintered body)
[0194] The sintered body sample was subjected to XRD measurement under the same conditions as those for the powder sample. The monoclinic ratio and monoclinic intensity ratio were calculated using "PRO-FIT" as the obtained XRD pattern and calculation program by equations (1) and (3), respectively.
[0195] In the XRD measurement, the following sintered body sample was used: after cutting the surface using a surface grinder, mirror polishing was performed in the order of automatic polishing based on water-resistant paper (No. 800), automatic polishing using diamond slurry with an average particle size of 3 μm, and automatic polishing based on 0.03 μm colloidal silica, thereby obtaining a sintered body sample with a surface roughness (Ra) ≤ 0.04 μm. The automatic polishing used an automatic polishing device (device name: MECATECH 334, manufactured by PRESI).
[0196] (Sintered body density)
[0197] The measured density of the sintered body sample was measured by the Archimedean method. Before the measurement, the mass of the dried sintered body was measured, and then the sintered body was placed in water and boiled for 1 hour as a pretreatment. The theoretical density was calculated according to equations (6) to (9), and the relative density (%) was calculated based on the value of the measured density (ρ) relative to the theoretical density (ρ0) as the sintered body density.
[0198] (Average crystal particle size)
[0199] The average grain size was determined by using a platform method using a SEM observation image of a sintered body sample obtained by field emission scanning electron microscopy. That is, a circle with a known area was drawn in the SEM observation image, and the number of grains in the circle (Nc) and the number of grains on the circumference of the circle (Ni) were measured.
[0200] Based on the total number of crystal grains (Nc+Ni) being 250±50, the average crystal grain size was determined using the following formula.
[0201] Average grain size = (Nc + (1 / 2) × Ni) / (A / M 2 )
[0202] In the above formula, Nc is the number of grains in the circle, Ni is the number of grains on the circumference of the circle, A is the area of the circle, and M is the magnification of the scanning electron microscope observation (5000 times). It should be noted that when the number of grains (Nc+Ni) in one SEM observation image is less than 200, (Nc+Ni) is set to 250±50 using multiple SEM observation images.
[0203] Before measurement, the sintered body samples were mirror-polished and then subjected to thermal etching as pretreatment. The mirror-polishing was performed by grinding the sintered body surface with a surface grinder and then using a mirror-polishing device with diamond abrasive grains of average particle sizes of 9 μm, 6 μm, and 1 μm, in sequence.
[0204] (Offset value)
[0205] Using a surface powder X-ray diffraction apparatus (apparatus name: Auto MATE, manufactured by Rigaku Corporation) equipped with CrKβ rays as a radiation source, the shift value of the tetragonal zirconia (113) plane was measured under the following conditions.
[0206] Radiation source: CrKα ray (λ=2.29100nm)
[0207] Accelerating voltage: 30 kV
[0208] Current: 30mA
[0209] Measurement method: Same inclination method
[0210] Collimator diameter: 4mm
[0211] Measuring lattice plane: tetragonal zirconium oxide (113) plane
[0212] Tilt angle ψ: 0° and 45°
[0213] According to the obtained 2θ (0°) and 2θ (45°) , find the offset value.
[0214] (Fracture toughness value)
[0215] The fracture toughness value of the sintered body sample was measured by the SEPB method specified in JIS R 1607. The measurement was performed using a columnar sintered body sample with a support distance of 30 mm, a width of 4 mm, and a thickness of 3 mm, and the average value of 10 measurements was taken as the fracture toughness value.
[0216] (Bending Strength)
[0217] The bending strength of the sintered body sample was measured by a three-point bending test based on JIS R 1601. The measurement was performed using a columnar sintered body sample with a support distance of 30 mm, a width of 4 mm, and a thickness of 3 mm, and the average value of 10 measurements was taken as the bending strength.
[0218] (Total light transmittance)
[0219] The total transmittance was measured using a spectrophotometer (device name: V-650, manufactured by JASCO Corporation) by a method based on JISK 7361. A disc-shaped sample was used for the measurement. Before the measurement, both sides of the sample were polished to a sample thickness of 1 mm and a surface roughness (Ra) of 0.02 μm or less. Light with a wavelength of 220 to 850 nm was passed through the sample and focused with an integrating sphere to measure the transmittance at each wavelength, and the transmittance at a wavelength of 600 nm was taken as the total transmittance.
[0220] The measurement conditions of the total light transmittance are as follows.
[0221] Bandwidth: 5.0nm
[0222] Data acquisition interval: 0.5nm
[0223] Scanning speed: 1000nm / min
[0224] Synthesis example 1
[0225] A zirconium oxychloride aqueous solution having a zirconium concentration and a chloride ion concentration of 0.4 mol / L was hydrolyzed. The hydrolyzed aqueous solution was ultrafiltered using an ultrafiltration membrane (molecular weight cutoff: 6000) to obtain a zirconium oxide sol having an average sol particle size of 250 nm. The W of the obtained zirconium oxide sol was Zr It was below the detection limit (0.01 mass % or less).
[0226] Yttrium chloride hexahydrate and ammonia solution were added to the ultrafiltered zirconium oxide sol aqueous solution in such a manner that yttrium oxide was 1.6 mol% to obtain a precipitate. The obtained precipitate was washed with pure water and dried in an air atmosphere, and then calcined in an air atmosphere at a calcination temperature of 1025°C for 2 hours to obtain a calcined powder. The BET specific surface area of the obtained calcined powder was 12.5 m 2 / g, and the crystallite diameter of the monoclinic crystal is 35nm.
[0227] After the calcined powder was mixed with pure water to form a slurry, it was ball-milled using zirconium oxide balls and dried in an atmospheric atmosphere at 120°C to obtain a powder consisting of zirconium oxide containing yttria with an yttria content of 1.6 mol%, which was used as the powder of this synthesis example. The yttria of the powder of this synthesis example was completely dissolved in zirconium oxide, and its crystal phase was monoclinic zirconium oxide and tetragonal zirconium oxide. In addition, the median particle size was 0.15 μm, and the volume particle size distribution curve was a bimodal distribution with peaks at particle sizes of 0.14 μm and 0.33 μm, and the particle size peak ratio was 0.39.
[0228] Synthesis example 2
[0229] A mixed powder of the calcined powder and the alumina sol containing 0.25 mass % of alumina in terms of Al2O3 was ball-milled, and a powder containing 0.25 mass % of alumina in terms of Al2O3 and the balance of 1.6 mol % of yttria in zirconium oxide was obtained by the same method as in Synthesis Example 1. The median particle size of the powder of this Synthesis Example was 0.15 μm, and the volume particle size distribution curve was a bimodal distribution having peaks at particle sizes of 0.14 μm and 0.32 μm, and the particle size peak ratio was 0.37.
[0230] Synthesis example 3
[0231] A powder containing 0.25 mass % of aluminum oxide calculated as Al2O3 and the balance being 1.6 mol % of yttrium oxide and zirconium oxide was obtained in the same manner as in Synthesis Example 1, except that the calcination temperature was set to 1130°C and the mixed powder of the calcined powder and 0.25 mass % of aluminum oxide sol calculated as Al2O3 was ball milled.
[0232] The BET specific surface area of the calcined powder was 6.7 m 2 / g, and the crystallite diameter of the monoclinic crystal was 44nm. In addition, the median particle size of the powder of this synthesis example was 0.18μm, and the volume particle size distribution curve was a bimodal distribution with peaks at particle sizes of 0.14μm and 0.36μm, and the particle size peak ratio was 0.85.
[0233] Synthesis example 4
[0234] In the ultrafiltered zirconium oxide sol aqueous solution, yttrium chloride hexahydrate was added in such a manner that yttrium oxide was 2 mol%, and a mixed powder of the calcined powder and the alumina sol in an amount of 0.25 mass % in terms of Al2O3 was ball-milled, and a powder containing 0.25 mass % of alumina in terms of Al2O3 and the balance of zirconium oxide containing 2 mol % of yttrium oxide was obtained in the same manner as in Synthesis Example 1. The median particle size of the powder of this Synthesis Example was 0.15 μm, and the volume particle size distribution curve was a bimodal distribution having peaks at particle sizes of 0.14 μm and 0.33 μm, and the particle size peak ratio was 0.33.
[0235] Synthesis example 5
[0236] In addition to ball milling the mixed powder of the calcined powder and the aluminum oxide powder with a content of 20% by mass calculated as Al2O3, a powder composed of zirconium oxide containing 20% by mass of aluminum oxide calculated as Al2O3 and the balance containing 1.6 mol% yttria was obtained in the same manner as in Synthesis Example 1. The median particle size of the powder in this synthesis example is 0.15 μm, and the volume particle size distribution curve is a bimodal distribution with peaks at particle sizes of 0.14 μm and 0.35 μm, and the particle size peak ratio is 0.41. In addition, the crystallite diameter (D t ) is 42nm.
[0237] Synthesis example 6
[0238] Except that the calcination temperature was set to 1130°C and the mixed powder of the calcined powder and the aluminum oxide powder with 20 mass % calculated as Al2O3 was ball-milled, a powder containing 20 mass % aluminum oxide calculated as Al2O3 and the balance being zirconium oxide containing 1.6 mol % yttria was obtained in the same manner as in Synthesis Example 1. The median particle size of the powder in this Synthesis Example was 0.16 μm, the volume particle size distribution curve was a bimodal distribution with peaks at particle sizes of 0.14 μm and 0.35 μm, and the particle size peak ratio was 0.67.
[0239] Synthesis Example 7
[0240] In the ultrafiltered zirconium oxide sol aqueous solution, yttrium chloride hexahydrate was added in such a manner that yttrium oxide was 2 mol%, and a mixed powder of the calcined powder and the alumina sol in an amount of 5 mass % in terms of Al2O3 was ball-milled, and a powder consisting of zirconium oxide containing 5 mass % of aluminum oxide in terms of Al2O3 and the balance containing 2 mol % of yttrium oxide was obtained by the same method as in Synthesis Example 1. The median particle size of the powder of this Synthesis Example was 0.15 μm, and the volume particle size distribution curve was a bimodal distribution having peaks at particle sizes of 0.14 μm and 0.35 μm, and the particle size peak ratio was 0.41.
[0241] Synthesis example 8
[0242] A mixed powder of the calcined powder and the alumina sol containing 0.5 mass % of alumina in terms of Al2O3 was ball-milled, and a powder containing 0.5 mass % of alumina in terms of Al2O3 and the balance of 1.6 mol % of yttria in zirconium oxide was obtained by the same method as in Synthesis Example 1. The median particle size of the powder of this Synthesis Example was 0.15 μm, and the volume particle size distribution curve was a bimodal distribution having peaks at particle sizes of 0.14 μm and 0.32 μm, and the particle size peak ratio was 0.49.
[0243] Synthesis example 9
[0244] A mixed powder of the calcined powder and 1 mass % of alumina sol calculated as Al2O3 was ball-milled, and a powder containing 1 mass % of alumina calculated as Al2O3 and the balance of 1.6 mol % of yttria in zirconium oxide was obtained by the same method as in Synthesis Example 1. The median particle size of the powder of this Synthesis Example was 0.15 μm, and the volume particle size distribution curve was a bimodal distribution with peaks at particle sizes of 0.14 μm and 0.34 μm, and the particle size peak ratio was 0.49.
[0245] Synthesis example 10
[0246] The calcined powder and the mixed powder of 0.25 mass % of germanium dioxide calculated as GeO2 were subjected to ball milling treatment. In addition, a powder containing 0.25 mass % of germanium dioxide calculated as GeO2 and the balance of zirconium oxide containing 1.6 mol % of yttria was obtained by the same method as in Synthesis Example 1. The median particle size of the powder of this synthesis example was 0.14 μm, and the volume particle size distribution curve was a bimodal distribution with peaks at particle sizes of 0.14 μm and 0.34 μm, and the particle size peak ratio was 0.37.
[0247] Synthesis example 11
[0248] A mixed powder of the calcined powder and the silica sol containing 0.25 mass % of SiO2 was ball-milled, and a powder containing 0.25 mass % of silica in terms of SiO2 and the balance of 1.6 mol % of yttria in zirconium oxide was obtained by the same method as in Synthesis Example 1. The median particle size of the powder of this Synthesis Example was 0.18 μm, and the volume particle size distribution curve was a bimodal distribution with peaks at particle sizes of 0.14 μm and 0.35 μm, and the particle size peak ratio was 0.89.
[0249] Synthesis example 12
[0250] The calcined powder and a mixed powder of 0.25 mass % alumina sol calculated as Al2O3 and 0.25 mass % germanium dioxide calculated as GeO2 were ball-milled, and a powder containing 0.25 mass % alumina calculated as Al2O3 and 0.25 mass % germanium dioxide calculated as GeO2, and the balance being zirconium oxide containing 1.6 mol % yttria, was obtained by the same method as in Synthesis Example 1. The median particle size of the powder of this Synthesis Example was 0.15 μm, and the volume particle size distribution curve was a bimodal distribution with peaks at particle sizes of 0.14 μm and 0.34 μm, and the particle size peak ratio was 0.37.
[0251] Comparative Synthesis Example 1
[0252] A zirconium oxychloride aqueous solution having a zirconium concentration and a chloride ion concentration of 0.37 mol / L and 0.74 mol / L, respectively, was hydrolyzed. The hydrolyzed aqueous solution was ultrafiltered using an ultrafiltration membrane (molecular weight cutoff: 6000) to obtain a zirconium oxide sol having an average sol particle size of 100 nm. The W of the obtained zirconium oxide sol Zr It is 9 mass %.
[0253] Yttrium chloride hexahydrate and ammonia solution were added to the ultrafiltered zirconium oxide sol aqueous solution so that yttrium oxide was 2 mol% to obtain a precipitate. The obtained precipitate was washed with pure water and dried in an air atmosphere, and then calcined in an air atmosphere at a calcination temperature of 1000° C. for 2 hours to obtain a calcined powder.
[0254] The calcined powder was mixed with pure water to form a slurry, and then ball-milled using zirconia balls. The slurry was then dried in an air atmosphere at 120°C to obtain a powder consisting of yttria-containing zirconia with an yttria content of 2 mol%, which was used as the powder for this comparative synthesis example.
[0255] Comparative Synthesis Example 2
[0256] A mixed powder of the calcined powder and 0.25 mass % alumina powder calculated as Al2O3 was ball-milled, and a powder containing 0.25 mass % alumina calculated as Al2O3 and the remainder being zirconium oxide containing 2 mol % yttria was obtained by the same method as in Comparative Synthesis Example 1.
[0257] Comparative Synthesis Example 3
[0258] A mixed powder of the calcined powder and 5 mass % of alumina powder calculated as Al2O3 was ball-milled, and a powder containing 5 mass % of alumina calculated as Al2O3 and the remainder being zirconium oxide containing 2 mol % of yttrium oxide was obtained by the same method as in Comparative Synthesis Example 1.
[0259] Comparative Synthesis Example 4
[0260] A powder composed of zirconium oxide containing 0.9 mol % of yttrium oxide was obtained by the same method as in Synthesis Example 1 except that yttrium chloride hexahydrate and an aqueous ammonia solution were added to the ultrafiltrated zirconium oxide sol aqueous solution so that yttrium oxide was 0.9 mol % to obtain a precipitate.
[0261] The following table shows the evaluation results of the powders of these synthesis examples and comparative synthesis examples.
[0262] [Table 1]
[0263]
[0264] As can be seen from the table above, in the synthesis examples and comparative synthesis examples 1-3, the stabilizer content (yttrium oxide content) and the additive content of any powder are the same, but compared with the synthesis examples, the D m Furthermore, it can be seen that D of Synthesis Example 4 is smaller than that of Synthesis Example 5. m Smaller.
[0265] Example 1
[0266] The powder of Synthesis Example 4 was pressed into a mold at a pressure of 70 MPa and CIP treated at a pressure of 196 MPa to obtain a molded body. The obtained molded body was subjected to normal pressure sintering for 2 hours in an air atmosphere at a sintering temperature of 1200°C to obtain a pre-sintered body. The pre-sintered body was subjected to HIP treatment for 1 hour in an argon atmosphere at a treatment pressure of 150 MPa and a treatment temperature of 1500°C to obtain a HIP treated body, which was then sintered in an air atmosphere at 1000°C for 1 hour to obtain a sintered body (HIP treated body) of this example.
[0267] Example 2
[0268] A molded body and a sintered body were obtained in the same manner as in Example 1 except that the powder of Synthesis Example 5 was used, the sintering temperature of the calcination was set to 1350°C, and the treatment temperature of the HIP treatment was set to 1500°C.
[0269] Example 3
[0270] A compact and a sintered body were obtained in the same manner as in Example 1 except that the powder of Synthesis Example 6 was used, the sintering temperature of the calcination was set to 1350°C, and the treatment temperature of the HIP treatment was set to 1500°C.
[0271] Example 4
[0272] A molded body and a sintered body were obtained by the same method as in Example 1 except that the powder of Synthesis Example 7 was used and the treatment temperature of the HIP treatment was 1500°C.
[0273] Example 5
[0274] A compact and a sintered body were obtained in the same manner as in Example 1 except that the powder of Synthesis Example 8 was used, the sintering temperature of the preliminary sintering was set to 1175°C, and the treatment temperature of the HIP treatment was set to 1250°C.
[0275] Example 6
[0276] A molded body and a sintered body were obtained in the same manner as in Example 1 except that the powder of Synthesis Example 9 was used, the sintering temperature of the preliminary sintering was set to 1175°C, and the treatment temperature of the HIP treatment was set to 1250°C.
[0277] Example 7
[0278] A molded body and a sintered body were obtained in the same manner as in Example 1 except that the powder of Synthesis Example 9 was used, the sintering temperature of the preliminary sintering was set to 1175°C, and the treatment temperature of the HIP treatment was set to 1350°C.
[0279] Example 8
[0280] A molded body and a sintered body were obtained in the same manner as in Example 1 except that the powder of Synthesis Example 10 was used, the sintering temperature of the preliminary sintering was set to 1200°C, and the treatment temperature of the HIP treatment was set to 1250°C.
[0281] Example 9
[0282] A compact and a sintered body were obtained in the same manner as in Example 1 except that the powder of Synthesis Example 12 was used, the sintering temperature of the preliminary sintering was set to 1175°C, and the treatment temperature of the HIP treatment was set to 1250°C.
[0283] Example 10
[0284] A molded body and a sintered body were obtained by the same method as in Example 1 except that the powder of Synthesis Example 2 was used and the treatment temperature of the HIP treatment was 1350°C.
[0285] The evaluation results of the sintered bodies of Examples are shown in the following table together with the relative density of the pre-sintered bodies.
[0286] [Table 2]
[0287]
[0288] According to the above table, it can be confirmed that the bending strength is greater than 1450MPa and the fracture toughness value is 6.0MPa·m 0.5 Furthermore, it was confirmed that the fracture toughness value was 7.0 MPa·m 0.5 The sintered body has a bending strength of 1460 MPa and a fracture toughness of 8.0 MPa·m 0.5 The sintered body has a bending strength of 1550 MPa.
[0289] Measurement Example 1 (Total Light Transmittance)
[0290] The total light transmittance of the sintered bodies of Examples was measured. The main results are shown in the following table.
[0291] [Table 3]
[0292]
[0293] According to the above table, it can be confirmed that the total light transmittance tends to decrease with the increase in the amount of additives. In addition, it can be confirmed that the total light transmittance when the additive is 0.25 mass % or more and 1.0 mass % or less is 25% or more, further 30% or more, and further 35% or more.
[0294] Measurement Example 2 (Offset Value)
[0295] The offset value of the sintered body of Example 10 was measured. In addition, for comparison, a commercially available zirconium oxide powder containing 2 mol% yttria (product name: TZ-2Y, manufactured by Tosoh Corporation) was used, and after pre-sintering at a sintering temperature of 1450°C, HIP treatment was performed at a treatment temperature of 1500°C to produce a sintered body (comparative sintered body) with the offset value measured. The results are shown in the table below.
[0296] [Table 4]
[0297]
[0298] Regarding the comparative sintered bodies produced by HIP treatment using commercially available powder, it was confirmed that the sintered body of Example 10 had high offset values and fracture toughness values.
[0299] Measurement Example 3 (Evaluation of Processability)
[0300] The sintered bodies of the examples were processed into samples with a thickness of 0.09 mm. All of the sintered bodies were able to be processed into measurement samples with a thickness of 0.09 mm without causing cracks or the like.
[0301] As a comparative measurement example, the powder of Comparative Synthesis Example 1 was pressed with a mold at a pressure of 70 MPa and CIP treated at a pressure of 196 MPa, and the obtained molded body was subjected to normal pressure sintering in an air atmosphere at a sintering temperature of 1450°C for 2 hours to obtain a sintered body. The sintered body was subjected to the same processing, but the sintered body was broken during the processing and could not be processed thinner. The thickness of the cracked sintered body piece was about 0.3 mm.
[0302] Measurement Example 4 (Evaluation of Composite Material)
[0303] The powders of Synthesis Examples 2 and 3 were used to prepare composites. That is, after drying the powder at 150°C for more than 1 hour, the powder and acrylic resin were added to a kneader (device name: Labonial TDR-3, manufactured by Toshin Corporation) in such a manner that the mass of the powder was 85% by mass relative to the mass of the obtained composite, and kneading was performed at 160°C to obtain a composite. After 15 minutes from the start of kneading, the torque (N·m) applied to the kneader was measured to evaluate the kneadability of the composite. The smaller the torque value, the easier it is to knead the composite, that is, the composite with better kneadability.
[0304] The flow rate of the composite sample was measured using a flow tester to evaluate the fluidity. A general flow tester (device name: flow tester CFT 500D, manufactured by Shimadzu Corporation) was used to fill the composite into a syringe. A load was applied to the composite under the following conditions, and the volume velocity (cm2) of the composite ejected from the syringe was measured. 3 The fluidity was confirmed by measuring the volume velocity. The measurement conditions are as follows. The larger the volume velocity value, the easier it is for the composite to flow in the molten state, that is, the composite has excellent fluidity.
[0305] Syringe area: 1cm 2
[0306] Die hole diameter: 1mm
[0307] Mould length: 2mm
[0308] Load: 50kg
[0309] Measuring temperature: 160℃
[0310] Composite density: 3.0g / cm 3
[0311] In addition, as a comparative measurement example, a BET specific surface area of 15.0 m 2 / g and an average particle size (median particle size) of 1.1μm and a zirconium oxide powder containing 3mol% yttria. The evaluation results of the composite are shown in the following table. It should be noted that the kneading properties of the powder of the comparative measurement example are low and cannot be kneaded at 160°C. Therefore, the kneading properties of the comparative measurement example in the following table represent the values when kneading is performed at 170°C.
[0312] [Table 5]
[0313]
[0314] Compared with the powder of the comparative measurement example, the powder of Synthesis Example 3 with a low BET specific surface area has excellent kneading properties and fluidity, and in particular, has significantly high fluidity. Furthermore, although the powders of Synthesis Example 2 and Comparative Measurement Example have the same degree of BET specific surface area, the fluidity of the powder of Synthesis Example 2 is very high compared with the powder of the comparative measurement example. From these results, it can be seen that the powder of the Synthesis Example also has excellent effects as a composition (composite) composed of powder and resin.
[0315] The entire contents of Japanese Patent Application No. 2020-075780 filed on April 22, 2020 and Japanese Patent Application No. 2020-178571 filed on October 26, 2020 including the specification, claims, and abstract are incorporated herein as the disclosed contents of the present specification.
Claims
1. A sintered body, characterized in that: The sintered body comprises zirconium oxide containing a stabilizer, wherein the monoclinic crystal ratio of the sintered body obtained by the following formula (1) is 0.5% or more, and the three-point bending strength obtained by a three-point bending test based on JIS R 1601 is greater than 1450 MPa, the content of the stabilizer is 1.0 mol% or more and less than 2.5 mol%, and the average crystal grain size of the zirconium oxide is 0.33 μm or more and 0.55 μm or less, The ratio of the area intensity of the XRD peak corresponding to the (11-1) plane of monoclinic zirconia to the area intensity of the XRD peak corresponding to the (111) plane of monoclinic zirconia, obtained by the following formula (3), is 0 or more and 10 or less, f m ={I m (111)+I m (11-1)} / [I m (111)+I m (11-1)+I t (111)+I c (111)]×100 (1) M (11-1) / (111) ={I m (11-1) / I m (111)} (3) In equations (1) and (3), f m is the monoclinic ratio expressed in %, M (11-1) / (111) is the monoclinic intensity ratio, I m (111) and I m (11-1) are the area intensities of the XRD peaks corresponding to the (111) and (11-1) planes of monoclinic zirconia, respectively. t (111) is the area intensity of the XRD peak corresponding to the (111) plane of tetragonal zirconia, and I c (111) is the area intensity of the XRD peak corresponding to the (111) plane of cubic zirconia.
2. The sintered body according to claim 1, wherein When the sample thickness is 1.0 mm, the total light transmittance with respect to light of a wavelength of 600 nm is 20% or more.
3. The sintered body according to claim 1 or 2, wherein The ratio of the area intensity of the XRD peak corresponding to the (11-1) plane of monoclinic zirconia to the area intensity of the XRD peak corresponding to the (111) plane of monoclinic zirconia is 0.75 or less.
4. The sintered body according to claim 1 or 2, wherein The stabilizer is one or more selected from the group consisting of yttrium oxide, calcium oxide, magnesium oxide and cerium oxide.
5. The sintered body according to claim 1 or 2, wherein The content of the stabilizer is 1.5 mol % or more and 1.8 mol % or less.
6. The sintered body according to claim 1 or 2, wherein The average grain size of the zirconium oxide crystal grains is 0.50 μm or more and 0.55 μm or less.
7. The sintered body according to claim 1 or 2, wherein The fracture toughness value measured by the method based on the SEPB method specified in JIS R 1607 is 6 MPa·m 0.5 Above and 11MPa·m 0.5 the following.
8. The sintered body according to claim 1 or 2, wherein The offset value of the tetragonal zirconia (113) plane is greater than 0.15°.
9. The sintered body according to claim 1 or 2, wherein: The sintered body contains one or more additional components selected from the group consisting of alumina, germanium dioxide, and silicon dioxide.
10. The sintered body according to claim 9, wherein The added component is aluminum oxide.
11. The sintered body according to claim 1 or 2, wherein The zirconium oxide includes monoclinic zirconium oxide, and at least any one of tetragonal zirconium oxide and cubic zirconium oxide.
12. The sintered body according to claim 1 or 2, wherein The ratio of the tetragonal crystal ratio of the sintered body after immersion treatment in hot water at 140° C. for 6 hours to the tetragonal crystal ratio before immersion treatment in hot water at 140° C. for 6 hours is 15% or more.
13. A method for producing a sintered body, wherein the sintered body is the sintered body according to any one of claims 1 to 12, the method comprising the following steps: A step of sintering a powder containing zirconium oxide having a monoclinic crystal ratio of greater than 70% and containing a stabilizer, wherein the crystallite diameter of the monoclinic zirconium oxide is greater than 23 nm and less than 80 nm, to produce a pre-sintered body having a relative density of less than 99%; and The process of pressurizing and sintering the pre-sintered body.
14. The manufacturing method according to claim 13, wherein: The pressure sintering is a hot isostatic pressing process.
15. A component comprising the sintered body according to claim 1 or 2.
Citation Information
Patent Citations
Zirconia sintered compact, sintering composition for the same and calcined object
JP2011178610A
ZrO2-Al2O3-BASED CERAMIC SINTERED BODY AND MANUFACTURING METHOD THEREFOR
JP2017226555A
Conveyance machine
JP2020075780A
Clip for attracting plant stem
JP2020178571A
Sintered ceramic material, powder composition for obtaining thereof, manufacturing process and ceramic pieces thereof
CN106170465A